Rates of dark CO2 fixation are driven by microbial biomass in a temperate forest soil. (November 2020) - Akinyede, Rachael; Taubert, Martin; Schrumpf, Marion; Trumbore, Susan; Küsel, Kirsten
Abstract: Soils substantially contribute to the terrestrial fluxes of CO2 to the atmosphere. Dark CO2 fixation, the microbial process by which pore space CO2 is reduced to organic matter, may recycle and trap some of the CO2 respired in soils before it can escape to the atmosphere. To evaluate its potential significance for global temperate forest soil carbon stocks, we quantified dark CO2 fixation rates in a temperate beech forest soil down to 1 m depth over a range of 2–20% (v:v) headspace CO2 concentrations, by tracing incorporation of a 13 C–CO2 label into microbial biomass carbon and soil organic matter. We found that fixation rates under a concentration of 2% CO2 decreased with depth from 0.86 to 0.06 μg C normalized to g(dw) soil −1 d −1 . However, when dark CO2 fixation rates were normalized to soil microbial biomass carbon, no significant differences between depths were observed. Higher CO2 concentrations increased fixation rates, with a linear 2-fold increase between 2% and 10% CO2 . Molecular analysis revealed the dominance of heterotrophs, along with the presence of autotrophs mainly employing the Calvin Benson Bassham (CBB) pathway followed by the reductive citric acid (rTCA) pathway. Although community composition varied with depth, the relative fraction of autotrophs determined by qPCR of RuBisCO ( cbbL IA, cbbL IC) and ATP-citrate lyase ( aclA ) genes remained stable at approximately 0.5% of the total community. Dark CO2 fixed carbon accounted for up to 1.1% of microbial biomass carbon and up to 0.035% of soil organic carbon after 28 days. We estimated a fixation flux of 25 ± 7.2 g C m −2 yr −1 to 1 m depth for the Hainich forest soil under field conditions. Without this process, Hainich forest soil CO2 emissions would be 5.6% higher, recycling a fraction of carbon large enough to potentially affect carbon isotope signatures in SOC. If this is held for all temperate forest soils globally, the annual rate of dark CO2 fixation would be 0.26 ± 0.07 Pg C yr −1 to a depth of 1 m, without considering contributions from other biomes. In conclusion, microbial biomass carbon and CO2 concentration appear to be the main drivers of dark CO2 fixation in temperate forest soils, and dark CO2 fixation may maintain Hainich forest soil carbon stocks by moderating a significant fraction of soil CO2 emissions annually. Highlights: Rates of dark CO2 fixation correlate with microbial biomass carbon down to 1 m soil depth. Dark CO2 fixation rates increase linearly with CO2 concentrations between 2 and 10%. Without an estimated CO2 fixation of 25 ± 7.2 g C m −2 yr −1, Hainich forest soil CO2 emission could be 5.6% higher.